On the role of residue phosphorylation in 14-3-3 partners: AANAT as a case study - Masone, Diego (Sci Rep, 2017)
Twenty years ago, a novel concept in protein structural biology was discovered: the intrinsically disordered regions (IDRs). These regions remain largely unstructured under native conditions and the more are studied, more properties are attributed to them. Possibly, one of the most important is their ability to conform a new type of protein-protein interaction. Besides the classical domain-to-domain interactions, IDRs follow a ‘fly-casting’ model including ‘induced folding’. Unfortunately, it is only possible to experimentally explore initial and final states. However, the complete movie of conformational changes of protein regions and their characterization can be addressed by in silico experiments. Here, we simulate the binding of two proteins to describe how the phosphorylation of a single residue modulates the entire process. 14-3-3 protein family is considered a master regulator of phosphorylated proteins and from a modern point-of-view, protein phosphorylation is a three component system, with writers (kinases), erasers (phosphatases) and readers. This later biological role is attributed to the 14-3-3 protein family. Our molecular dynamics results show that phosphorylation of the key residue Thr31 in a partner of 14-3-3, the aralkylamine N-acetyltransferase, releases the fly-casting mechanism during binding. On the other hand, the non-phosphorylation of the same residue traps the proteins, systematically and repeatedly driving the simulations into wrong protein-protein conformations.